Tepung ulat sagu (Rhyinchophorus ferrugineus) imunomodulator Nitric Oxide (NO) sirkulasi mencit terapi antimalaria standar - Ariani, Ariani; Anjani, Gemala; Sofro, Muchlis Achsan Udji; Djamiatun, Kis (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2018)
Background : Sago worm flour (Rhyinchophorus ferrugineus)is a coconut beetle larvae that is processed into flour.This flour contains antioxidants as well as arginine, both of which play a role in modulating oxidative stress including NO involved in immunopathology of cerebral malaria.Objectives : To prove the immunomodulator role of sago worm flour in decreasing circulation NO level at mice who received standard antimalarial therapy Dihydroartemisinin Piperaquine (DHP)Methods : This study was randomized control group post test only design by using 23 Swiss mice which divided into 5 group consist of : K(-) normal mice; K(+) inoculated woth Plasmodium berghei ANKA (PbA); X1 received DHP; X2 received sago worm flour; X3 received both of sago worm flour and DHP. All treatment groups X1,X2 and X3 were inoculated by PbA before treatmen were given. Serum circulation NO level was assessed by ELISA. statistical analysis used was One Way ANOVA followed by Bonferroni post hoc test.Results : The mean NO level in K(-), K(+), X1, X2, and X3 were 1.008 μmol/mL, K(+) 1.338 μmol/mL; while at treatment X1 1.143 μmol/mL, X2 1.410 μmol/mL, dan X3 0.886 μmol/mL. One way ANOVA showed that they were significantly different (p=0.001). Bonferroni post hoc test of X2 was proportional to K(+) (p=1.000), whole had NO level lower than either K(+)(p=0.009) or X2 (p=0.002). Conclusion : The immunomodulatory effects of sago worm flour (Rhyinchophorus ferrugineus) reduced circulating NO levels in standard antimalarial therapy recipients.